If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 62 = 5x + 34 Reorder the terms: 62 + 9x = 5x + 34 Reorder the terms: 62 + 9x = 34 + 5x Solving 62 + 9x = 34 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 62 + 9x + -5x = 34 + 5x + -5x Combine like terms: 9x + -5x = 4x 62 + 4x = 34 + 5x + -5x Combine like terms: 5x + -5x = 0 62 + 4x = 34 + 0 62 + 4x = 34 Add '-62' to each side of the equation. 62 + -62 + 4x = 34 + -62 Combine like terms: 62 + -62 = 0 0 + 4x = 34 + -62 4x = 34 + -62 Combine like terms: 34 + -62 = -28 4x = -28 Divide each side by '4'. x = -7 Simplifying x = -7
| 2a+3b=12 | | -13x-119=-7x-71 | | 15-7=n | | 3x+24=12x-48 | | -12x-98=-8x-62 | | 3x+13=42-2x | | 2d+9d=5 | | -12x+38=-7x+23 | | 4x^3=100 | | -10x+111=-5x+71 | | 14x=3y | | (11m^2+2m-6)-(4m^2+m-1)= | | -8x-37=-5x-19 | | 8x^2+12y^2=96 | | 5x+28=13x+52 | | y=2x^2+x-3 | | 5x+28=13x-25 | | 13-10x=78-45 | | 15x+98=10x+58 | | 100+x^2=2x | | 1*49=7(x-6) | | -0.4h=-3 | | 1*49=7*(x-6) | | 3x^2-6x+4=0 | | -6[h-4]=-24 | | 7m-30=-3m+10 | | 5=2-3c | | 5x*30=10*(-21) | | 0.25x+5.00=300 | | 5n=2-3n | | -4(0)+2y=-4 | | 5n+7=62 |